The Effect of Social Media Marketing on VCO Purchasing Decisions at Osseda Folala Cooperative - Kristian Putra Waruwu, Advent; Laila, Otanius; Mendrofa, Yupiter; Zalukhu, Yuterlin (Manunggal Halim Jaya, 2025)
This study aims to analyze the effect of social media marketing on purchasing decisions (VCO) at Osseda Folala Nias Cooperative. Social media has become an effective tool in improving marketing and influencing consumer purchasing decisions. This research uses a quantitative method with a coefficient of determination test approach to evaluate how much social media marketing influences purchasing decisions. Based on the coefficient of determination test results, the Adjusted R Square value of 0.555 indicates that the social media marketing variable (X) can explain the purchasing decision variable (Y) by 55.5% after adjusting for the sample and independent variables. Other variables outside this study influence the remaining 44.5%. The results of this study indicate that marketing strategies through social media significantly influence VCO purchasing decisions at Osseda Folala Nias Cooperative. However, other factors also need to be considered to increase marketing effectiveness.